The Vacuolating Autotransporter Toxin (Vat) of Escherichia coli Causes Cell Cytoskeleton Changes and Produces Non-lysosomal Vacuole Formation in Bladder Epithelial Cells - Díaz, Juan Manuel; Dozois, Charles M.; Avelar-González, Francisco Javier; Hernández-Cuellar, Eduardo; Pokharel, Pravil; de Santiago, Alfredo Salazar; Guerrero-Barrera, Alma Lilian (Frontiers in Cellular and Infection Microbiology, 2020)
Urinary tract infections (UTIs) affect more than 150 million people, with a cost of over 3.5 billion dollars, each year. Escherichia coli is associated with 70–80% of UTIs. Uropathogenic E. coli (UPEC) has virulence factors including adhesins, siderophores, and toxins that damage host cells. Vacuolating autotransporter toxin (Vat) is a member of serine protease autotransporter proteins of Enterobacteriaceae (SPATEs) present in some uropathogenic E. coli (UPEC) strains. Vat has been identified in 20–36% of UPEC and is present in almost 68% of urosepsis isolates. However, the mechanism of action of Vat on host cells is not well-known. Thus, in this study the effect of Vat in a urothelium model of bladder cells was investigated. Several toxin concentrations were tested for different time periods, resulting in 15–47% of cellular damage as measured by the LDH assay. Vat induced vacuole formation on the urothelium model in a time-dependent manner. Vat treatment showed loss of the intercellular contacts on the bladder cell monolayer, observed by Scanning Electron Microscopy. This was also shown using antibodies against ZO-1 and occludin by immunofluorescence. Additionally, changes in permeability of the epithelial monolayer was demonstrated with a fluorescence-based permeability assay. Cellular damage was also evaluated by the identification of cytoskeletal changes produced by Vat. Thus, after Vat treatment, cells presented F-actin distribution changes and loss of stress fibers in comparison with control cells. Vat also modified tubulin, but it was not found to affect Arp3 distribution. In order to find the nature of the vacuoles generated by Vat, the Lysotracker deep red fluorescent dye for the detection of acidic organelles was used. Cells treated with Vat showed generation of some vacuoles without acidic content. An ex vivo experiment with mouse bladder exposed to Vat demonstrated loss of integrity of the urothelium. In conclusion, Vat induced cellular damage, vacuole formation, and urothelial barrier dysregulation of bladder epithelial cells. Further studies are needed to elucidate the role of these vacuoles induced by Vat and their relationship with the pathogenesis of urinary tract infection.